Acute effect of different doses of caffeinated chewing gum on exercise performance in caffeine-habituated male soccer players - Yildirim, Ulas Can; Akcay, Neslihan; Alexe, Dan Iulian; Esen, Ozcan; Gulu, Mehmet; Cîrtiţă-Buzoianu, Cristina; Cinarli, Fahri Safa; Cojocaru, Marilena; Sari, Cengizhan; Alexe, Cristina Ioana; Karayigit, Raci (Frontiers in Nutrition, 2023)
The ergogenic benefits of caffeine have been well established, but there is scarce research with its chewing gum form. The aim of the present research was to examine the effects of various doses (100 and 200 mg) of caffeinated chewing gum on muscle strength, vertical jump performance and ball kicking speed in trained male soccer players. In a double-blind, randomized counterbalanced and crossover research design, 14 male soccer players (age = 22 ± 2 y; body mass = 74.2 ± 7.1 kg; height = 180.0 ± 6.8 cm; habitual caffeine intake = 358.9 ± 292.4 mg/day) participated three experimental trials. In each trial, participants performed isometric handgrip strength, quadriceps and hamstring strength, ball kicking speed and 15 s countermovement jump test 10 min after chewing of 100 mg (LCAF) or 200 mg (MCAF) of caffeinated gum or placebo (PLA). MCAF improved quadriceps strength (53.77 ± 5.77 kg) compared to LCAF (49.62 ± 8.81 kg, p = 0.048) and PLA (49.20 ± 7.20 kg, p = 0.032). However, either LCAF or MCAF had no significant effect on isometric handgrip and hamstring strength, ball kicking speed and 15 s countermovement jump test (all p > 0.05). These findings support chewing gum as an alternative mode of caffeine administration which can be used as a nutritional ergogenic aid for trained soccer players, at least for the quadriceps strength.